Chemical Composition of Hydrodistillation and Solvent Free Microwave Extraction of Essential Oils from Plectranthus amboinicus and Melaleuca cajupati Leaves and their Repellent Activity - Rabiatul Adawiyah Mohd Darwis; Mohd Izzat Arslan Che Ros; Nurafiqah Farhana Muhd Yazid; Fadhlina Che Ros (Trans Tech Publications Ltd, 2024)
Non-Indexed Publication